The neural determinants of beauty. (8th December 2021) - Yang, Taoxi; Formuli, Arusu; Paolini, Marco; Zeki, Semir
Abstract: The perception of faces correlates with activity in a number of brain areas, but only when a face is perceived as beautiful is the medial orbitofrontal cortex (mOFC) also engaged. Here, we enquire whether it is the emergence of a particular pattern of neural activity in face perceptive areas during the experience of a face as beautiful that determines whether there is, as a correlate, activity in mOFC. Seventeen subjects of both genders viewed and rated facial stimuli according to how beautiful they perceived them to be while the activity in their brains was imaged with functional magnetic resonance imaging. A univariate analysis revealed parametrically scaled activity within several areas, including the occipital face area (OFA), fusiform face area (FFA) and the cuneus; the strength of activity in these areas correlated with the declared intensity of the aesthetic experience of faces; multivariate analyses showed strong patterns of activation in the FFA and the cuneus and weaker patterns in the OFA and the posterior superior temporal sulcus (pSTS). The mOFC was only engaged when specific patterns of activity emerged in these areas. A psychophysiological interaction analysis with mOFC as the seed area revealed the involvement of the right FFA and the right OFA. We conjecture that it is the collective specific pattern‐based activity in these face perceptive areas, with activity in the mOFC as a correlate, that constitutes the neural basis for the experience of facial beauty, bringing us a step closer to understanding the neural determinants of aesthetic experience. Abstract : We investigated cortical representations related to facial beauty, hypothesising that the experience of beauty leads to the emergence of distinctive patterns in core areas dedicated to face perception and that it is only when such patterns emerge that there is a co‐activation of the medial orbito‐frontal cortex (mOFC), in which activity always correlates with the experience of beauty. This is precisely what we found: the occipital face area (OFA), fusiform face area (FFA), superior temporal sulcus (pSTS), cuneus, showed distinctive neural patterns during the judgments of beauty, while the insula showed patterns corresponding to not beautiful faces. A further connectivity analysis with mOFC as the seed area revealed the involvement of the right FFA and the right OFA.